Causal association between circulating inflammatory proteins and peripheral artery disease: a bidirectional two-sample Mendelian randomization study - Zhao, Juncheng; Sun, Bo; Huang, Shujie; Chen, Yunhui; Yan, Jingqiang (Frontiers in Immunology, 2024)
Introduction: A growing body of research has shown a strong connection between circulating inflammatory proteins and Peripheral artery disease (PAD). However, the causal relationship between circulating inflammatory proteins and PAD is still not fully understood. To investigate this association, we conducted a bidirectional Mendelian randomization study.Materials and Methods: Our study utilized genetic variation data obtained from genome-wide association studies (GWAS) datasets. Specifically, the GWAS dataset related to PAD (identifier: finn-b-I9_PAD) included 7,098 cases and 206,541 controls. Additionally, we extracted data on 91 inflammatory proteins from another GWAS dataset (identifiers: GCST90274758-GCST90274848), involving 14,824 participants. To assess the causal relationship between circulating inflammatory proteins and PAD development, we employed methodologies such as inverse variance weighting (IVW), MR Egger regression, and the weighted median approach. Furthermore, sensitivity analyses were conducted to ensure the reliability and robustness of our findings.Results: Two inflammatory proteins were found to be significantly associated with PAD risk: Natural killer cell receptor 2B4 levels (OR, 1.